2011
DOI: 10.2527/jas.2011-3836
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations between feed efficiency measured in a performance test station and performance of growing cattle in commercial beef herds

Abstract: Interest in selection for improved feed efficiency is increasing, but before any steps are taken toward selecting for feed efficiency, correlations with other economically important traits must first be quantified. The objective of this study was to quantify the genetic associations between feed efficiency measured during performance testing and linear type traits, BW, live animal value, and carcass traits recorded in commercial herds. Feed efficiency data were available on 2,605 bulls from 1 performance test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
(59 reference statements)
4
29
0
Order By: Relevance
“…Although bulls of low and high RFI in the current study had similar carcass conformation, which reflects similar LD depth, the negative correlation between RFI and carcass conformation score concurs with Crowley et al (2011) who found that RFI had a negative genetic correlation with carcass conformation (r = − 0.21), arising from improved muscularity in low RFI animals. A meta-analysis of genetic correlations between RFI and carcass conformation score by Berry and Crowley (2013) found that, in general, RFI tends to be negatively correlated with carcass conformation in beef cattle.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Although bulls of low and high RFI in the current study had similar carcass conformation, which reflects similar LD depth, the negative correlation between RFI and carcass conformation score concurs with Crowley et al (2011) who found that RFI had a negative genetic correlation with carcass conformation (r = − 0.21), arising from improved muscularity in low RFI animals. A meta-analysis of genetic correlations between RFI and carcass conformation score by Berry and Crowley (2013) found that, in general, RFI tends to be negatively correlated with carcass conformation in beef cattle.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies with bulls have shown that high RFI animals have a greater content of subcutaneous body fat than those of low RFI (Lancaster et al, 2009;Smith et al, 2010;Kelly et al, 2011). Similarly, Crowley et al (2011) found that RFI had a positive phenotypic (r = 0.26; P < 0.05) and genetic (r = 0.39) correlation with fat depth in bulls. However, in the current study, RFI had no significant effect on ribfat, backfat or rump fat depth.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Studies with heifers (Kelly et al, 2010a), beef cows (Lawrence et al, 2011a) and steers (Basarab et al, 2003;Nkrumah et al, 2004) found that animals ranked on the basis of RFI did not differ in morphological size. Similarly, Crowley et al (2011) found no significant genetic correlation between RFI and skeletal measurements; however, they did detect a negative phenotypic correlation (P , 0.05) between RFI and pelvis length (r 5 20.15) and width of hips (r 5 20.19).…”
Section: Lawrence Kenny Earley and Mcgeementioning
confidence: 94%
“…The statistical analysis of large beef cattle databases has clearly revealed heritable genetic differences in many animal characteristics including animal growth rate (Burfening et al, 1981;Arthur et al, 2001;Crowley et al, 2011), carcass conformation (Evans et al, 2007;Pabiou et al, 2009), feed intake and efficiency (Bouquet et al, 2009;Berry and Crowley, 2012;Berry and Crowley, 2013), and reproductive performance (Phocas and Sapa 2004;Berry and Evans, 2014). The impact of animal genetic differences for performance traits on subsequent phenotypic performance has been documented in controlled experiments that compared animals divergent in genetic merit for an individual trait (Crews et al, 2006;Keane and Diskin, 2007;Campion et al, 2009) or a combination (i.e.…”
Section: Introductionmentioning
confidence: 99%